1981
DOI: 10.1111/j.1365-2842.1981.tb00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental microleakage around ageing dental amalgam restorations: a review

Abstract: In vitro and in vivo experimental microleakage around ageing dental amalgam restorations has been reviewed. The methodologies, materials and results were examined and discussed. The initial experimental microleakage which occurred around unlined/unvarnished dental amalgam restorations and the development of leakage around lined/varnished dental amalgam restorations underlines the problem of attaining a permanent effective seal around dental amalgam restorations. The limitations of microleakage studies have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, long-term sealing capabilities of cavity varnish have been questioned (Jodaikin, 1981). A pilot study (Ben-Amar et al 1987) showed that microleakage in fresh Class V amalgam restorations can be almost totally eliminated at both enamel and dentine/cementum margins using light-cured Scotchbond Dental Adhesive (3M Company, Dental Products, St Paul, MN 55144, U.S.A.) as an interfacial sealer prior to insertion of spherical high-copper amalgam.…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term sealing capabilities of cavity varnish have been questioned (Jodaikin, 1981). A pilot study (Ben-Amar et al 1987) showed that microleakage in fresh Class V amalgam restorations can be almost totally eliminated at both enamel and dentine/cementum margins using light-cured Scotchbond Dental Adhesive (3M Company, Dental Products, St Paul, MN 55144, U.S.A.) as an interfacial sealer prior to insertion of spherical high-copper amalgam.…”
Section: Introductionmentioning
confidence: 99%
“…10 Because of the difference in thermal expansion coefficients of amalgam and tooth structures, intraoral temperature changes result in intermitting opening and closing of the gap thus creating inward and outward transport of fluid (percolation) along the amalgam-tooth interface. [11][12][13] This way dentin is easily exposed to the components of saliva, food, drinks, and products from bacterial metabolism.Exposure of amalgam fillings to the aggressive oral environment results in a complex of physical and chemical challenges that causes alterations of structure and properties e.g. time,…”
mentioning
confidence: 99%
“…A crevice exists at the freshly condensed amalgam-tooth interface, or it may develop after varnishes under aged dental amalgam restorations craze or arc lost (Jodaikin, 1981). This crevice is sufficiently wide for micro-organisms and oral fluids to pass along the cavity walls as marginal leakage which facilitates the development of dental caries at the interface and thereby accounts for the majority of amalgam restoration replacements (Richardson and Boyd, 1973).…”
Section: Introductionmentioning
confidence: 98%